Highly conserved influenza T cell epitopes induce broadly protective immunity. Issue 36 (23rd August 2019) - Eickhoff, Christopher S.; Terry, Frances E.; Peng, Linda; Meza, Krystal A.; Sakala, Isaac G.; Van Aartsen, Daniel; Moise, Leonard; Martin, William D.; Schriewer, Jill; Buller, R. Mark; De Groot, Anne S.; Hoft, Daniel F.
Highlights: Approach used here can be expanded to generate flu vaccine with universal relevance. Identified T cell epitopes induced heterologous protection in HLA transgenic mice. Conserved flu putative immunogenic sequences were identified via immunoinformatics. Predicted HLA-A2 and pan-DR-restricted epitopes immunogenic in HLA-transgenic mice. Predicted CD4 and CD8 epitopes induced effector function in human T cells. Abstract: Influenza world-wide causes significant morbidity and mortality annually, and more severe pandemics when novel strains evolve to which humans are immunologically naïve. Because of the high viral mutation rate, new vaccines must be generated based on the prevalence of circulating strains every year. New approaches to induce more broadly protective immunity are urgently needed. Previous research has demonstrated that influenza-specific T cells can provide broadly heterotypic protective immunity in both mice and humans, supporting the rationale for developing a T cell-targeted universal influenza vaccine. We used state-of-the art immunoinformatic tools to identify putative pan-HLA-DR and HLA-A2 supertype-restricted T cell epitopes highly conserved among > 50 widely diverse influenza A strains (representing hemagglutinin types 1, 2, 3, 5, 7 and 9). We found influenza peptides that are highly conserved across influenza subtypes that were also predicted to be class I epitopes restricted by HLA-A2. These peptides were found to be immunoreactive in HLA-A2 positive but not HLA-A2 negative individuals. Class II-restricted T cell epitopes that were highly conserved across influenza subtypes were identified. Human CD4 + T cells were reactive with these conserved CD4 epitopes, and epitope expanded T cells were responsive to both H1N1 and H3N2 viruses. Dendritic cell vaccines pulsed with conserved epitopes and DNA vaccines encoding these epitopes were developed and tested in HLA transgenic mice. These vaccines were highly immunogenic, and more importantly, vaccine-induced immunity was protective against both H1N1 and H3N2 influenza challenges. These results demonstrate proof-of-principle that conserved T cell epitopes expressed by widely diverse influenza strains can induce broadly protective, heterotypic influenza immunity, providing strong support for further development of universally relevant multi-epitope T cell-targeting influenza vaccines.